A kind of iron slag biochar composite material and its preparation method and application

By performing two pyrolysis methods in the protective gas, iron slag biochar composites are prepared, which solves the problem that nano zero-valent iron is susceptible to the environment, and achieves efficient removal of heavy metals and organic matters in water. It is suitable for a wide range of pH conditions.

CN116020396BActive Publication Date: 2025-02-11HUNAN UNIV

Patent Information

Application Number
CN202211308531.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-02-11
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

The existing iron slag biochar composites produce nano zero-valent iron during the pyrolysis process, resulting in the catalytic effect being affected by the environment and being unsatisfactory.

Method used

The iron slag biochar composite material was prepared by performing the first pyrolysis of the biomass to obtain the original biochar, and mixed with the acidified iron slag and performing the second pyrolysis. This method performs pyrolysis in the protective gas to avoid the formation of nano zero-valent iron.

Benefits of technology

The prepared iron slag biochar composite material exhibits excellent processing efficiency in removing heavy metals and organic matter from water, and works stably under a wide range of pH conditions, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116020396B_ABST
    Figure CN116020396B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of iron-doped biochar composite materials, and provides an iron slag biochar composite material and a preparation method and application thereof. The preparation method comprises the following steps: subjecting biomass to a first pyrolysis to obtain raw biochar; subjecting the raw biochar to acidification and mixing with iron slag and then subjecting the raw biochar to a second pyrolysis to obtain an iron slag biochar composite material; the first pyrolysis and the second pyrolysis are both carried out in a protective gas. The preparation method of the present invention is easy to operate and has a simple process. The prepared iron slag biochar composite material has the advantages of being green, efficient, and targeted, and can be used to activate persulfate to remove heavy metals and organic pollutants in water bodies, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of iron-doped biochar composite materials, and in particular to an iron slag biochar composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of global industry and agriculture, the wanton exploitation of mines, the abuse of various mineral processing agents, pesticides and antibiotics, the pollution of heavy metals and organic matter has become increasingly serious worldwide, which has posed a huge threat to human life and safety. At present, the treatment of heavy metal pollution in water mainly includes adsorption, ion exchange, phytoremediation, chemical precipitation, advanced oxidation and other means, and the treatment of organic pollution in water mainly includes photocatalysis, electrocatalysis, advanced oxidation and other means.

[0003] Nano-zero-valent iron is widely used in the redox adsorption of heavy metals in water and the activation of persulfate to degrade organic matter due to its ultra-high redox potential and activity. It is precisely because of the high activity of nano-zero-valent iron that its practical application is greatly limited, because nano-zero-valent iron easily reacts with oxygen or water molecules in the air, making it difficult to play the ideal catalytic role normally. Therefore, using a carrier to load nano-zero-valent iron to make it work normally has become a hot research direction.

[0004] Advanced oxidation processes usually use highly active substances produced by photocatalysis, electrochemistry or superoxide to oxidize and destroy organic molecules. This method has the effect of efficiently oxidizing heavy metals and removing organic matter. Zero-valent iron-biochar composites are considered to be adsorbents for efficient removal of heavy metals from water, and catalysts for removing organic matter such as activated persulfate to produce sulfate radicals, hydroxyl radicals, and singlet oxygen. However, in general, the effects of using iron slag to adsorb heavy metals and activate persulfate are not ideal, because during the pyrolysis of iron slag biochar composites, iron will be reduced to form nano zero-valent iron, which affects its ideal catalytic effect.

[0005] Therefore, how to obtain an iron slag-biochar composite material that has an adsorption effect on heavy metals and can activate persulfate to remove organic matter has become an urgent problem that technicians in this field need to solve. Summary of the invention

[0006] In view of this, the present invention provides an iron slag biochar composite material and a preparation method and application thereof, the main purpose of which is to solve the technical problems that zero-valent iron is easily affected by the environment, resulting in its inability to exert excellent catalytic effects.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The present invention provides a method for preparing an iron slag biochar composite material, comprising the following steps:

[0009] The biomass is subjected to a first pyrolysis to obtain raw biochar; the raw biochar is acidified and mixed with iron slag and then subjected to a second pyrolysis to obtain an iron slag biochar composite material;

[0010] The first pyrolysis and the second pyrolysis are both carried out in a protective gas.

[0011] Furthermore, the biomass is one or more of ramie stalks, ramie silk, wood chips and coffee grounds; and the particle size of the biomass is 50 to 200 meshes.

[0012] Furthermore, the temperature of the first pyrolysis is 300-500°C, the time of the first pyrolysis is 2-3h, and the heating rate from room temperature to the temperature of the first pyrolysis is 5-10°C / min.

[0013] Furthermore, the iron slag is the iron-containing surface skin that falls off the surface of factory smelting waste.

[0014] Furthermore, the mass ratio of the original biochar to the iron slag is 1 to 5:1.

[0015] Furthermore, the specific operation steps of the acidification and mixing are: placing the original biochar and iron slag into a mixed solution of concentrated nitric acid and water, until the mixed solution covers the original biochar and iron slag, and standing for 4 to 12 hours;

[0016] The volume ratio of the concentrated nitric acid to water is 1-3:1, and the concentration of the concentrated nitric acid is 2.4-7.2 mol / L.

[0017] Furthermore, the temperature of the second pyrolysis is 500-900°C, the time of the second pyrolysis is 2-3h, and the heating rate from room temperature to the temperature of the second pyrolysis is 5-10°C / min.

[0018] Furthermore, the protective gas is any one of nitrogen, helium, neon and argon.

[0019] The invention provides an iron slag biochar composite material prepared by the above preparation method.

[0020] The present invention also provides the use of the iron slag biochar composite material in activating persulfate to remove heavy metals and organic pollutants in water bodies.

[0021] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:

[0022] (1) The raw materials used in the present invention are all waste, including biomass and iron slag, which reduces the preparation cost and improves the yield;

[0023] (2) The iron slag biochar composite material prepared by the present invention has no pH requirement for application, can work normally under a very wide pH condition, and has excellent treatment efficiency in removing heavy metals and organic matter from water bodies;

[0024] (3) The process of the present invention is very simple, has strong operability, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The SEM images of the iron slag biochar composite material and the original sawdust biochar prepared in Example 1, wherein Figure a is the prepared iron slag biochar composite material, and Figure b is the original sawdust biochar;

[0026] Figure 2 This is a SEM image of the iron slag biochar composite material prepared in Example 1 after persulfate activation to remove trivalent arsenic and butyl xanthate;

[0027] Figure 3 This is a comparison chart of the removal rate of butyl xanthate by the iron slag biochar composite material prepared in Example 1 at different pH values;

[0028] Figure 4 This is a comparison chart of the removal rate of trivalent arsenic by the iron slag biochar composite material prepared in Example 1 at different pH values;

[0029] Figure 5 This is a comparison chart of the residual rates of butyl xanthate obtained when the iron slag biochar composite material prepared in Example 1 treats a mixture of butyl xanthate and trivalent arsenic in different proportions;

[0030] Figure 6 This is a comparison chart of the residual rates of trivalent arsenic obtained when the iron slag biochar composite material prepared in Example 1 treats mixtures of butyl xanthate and trivalent arsenic in different proportions. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing an iron slag biochar composite material, comprising the following steps:

[0032] The biomass is subjected to a first pyrolysis to obtain raw biochar; the raw biochar is acidified and mixed with iron slag and then subjected to a second pyrolysis to obtain an iron slag biochar composite material;

[0033] The first pyrolysis and the second pyrolysis are both carried out in a protective gas.

[0034] In the present invention, the biomass is one or more of ramie stalks, ramie silk, sawdust and coffee grounds, preferably sawdust, coffee grounds or ramie stalks, and more preferably sawdust; the particle size of the biomass is 50-200 mesh, preferably 80-180 mesh, and more preferably 100-150 mesh.

[0035] In the present invention, the temperature of the first pyrolysis is 300-500°C, preferably 330-460°C, and more preferably 380-420°C; the time of the first pyrolysis is 2-3h, preferably 2.2-2.8h, and more preferably 2.4-2.6h; the heating rate from room temperature to the temperature of the first pyrolysis is 5-10°C / min, preferably 6-9°C / min, and more preferably 7-8°C / min.

[0036] In the present invention, the iron slag is the iron-containing surface skin that falls off the surface of factory smelting waste.

[0037] In the present invention, the mass ratio of the raw biochar to the iron slag is 1 to 5:1, preferably 2 to 4:1, and more preferably 3:1.

[0038] In the present invention, the specific operation steps of the acidification mixing are: putting the original biochar and iron slag into a mixed solution of concentrated nitric acid and water, until the mixed solution covers the original biochar and the iron slag, and standing for 4 to 12 hours; the standing time is preferably 5 to 10 hours, and more preferably 7 to 9 hours.

[0039] In the present invention, the volume ratio of concentrated nitric acid to water is 1-3:1, preferably 2:1; the concentration of concentrated nitric acid is 2.4-7.2 mol / L, preferably 3-6 mol / L, and more preferably 4-5 mol / L.

[0040] In the present invention, the temperature of the second pyrolysis is 500-900°C, preferably 600-800°C, and more preferably 650-750°C; the time of the second pyrolysis is 2-3h, preferably 2.2-2.8h, and more preferably 2.4-2.6h; the heating rate from room temperature to the temperature of the second pyrolysis is 5-10°C / min, preferably 6-9°C / min, and more preferably 7-8°C / min.

[0041] In the present invention, the protective gas is any one of nitrogen, helium, neon and argon, preferably nitrogen or argon, and more preferably nitrogen.

[0042] The invention provides an iron slag biochar composite material prepared by the above preparation method.

[0043] The present invention also provides the use of the iron slag biochar composite material in activating persulfate to remove heavy metals and organic pollutants in water bodies. The persulfate is preferably peroxymonosulfate or peroxydisulfate, and more preferably peroxydisulfate.

[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Example 1

[0046] The sawdust was naturally air-dried and then ground and sieved. The sawdust residue powder between 100 mesh and 200 mesh was put into a tubular furnace and pyrolyzed for the first time under a nitrogen atmosphere. The heating rate during pyrolysis was 10°C / min. After the temperature reached 500°C, it was kept warm for 2h and then naturally cooled to room temperature to obtain the original sawdust biochar.

[0047] The original sawdust biochar was mixed with iron slag in a mass ratio of 3:1, put into a nitric acid solution prepared with ultrapure water and concentrated nitric acid in a volume ratio of 1:1, and allowed to stand for 4 hours. Then it was taken out and dried and put into a tubular furnace for a second pyrolysis under a nitrogen atmosphere. The heating rate during pyrolysis was 10℃ / min. After the temperature reached 900℃, it was kept warm for 2 hours and then naturally cooled to room temperature to obtain an iron slag biochar composite material, named ISBC.

[0048] Figure 1 The SEM images of the iron slag biochar composite material and the original sawdust biochar prepared in this example, Figure a is the prepared iron slag biochar composite material, and Figure b is the original sawdust biochar. Figure 1 It can be seen that after the modification step of the present invention, it can be clearly seen that spherical zero-valent iron is loaded on the surface of the biochar.

[0049] Example 2

[0050] The coffee grounds were naturally air-dried and then ground and sieved. The coffee grounds powder between 100 mesh and 200 mesh was put into a tubular furnace and pyrolyzed for the first time under a nitrogen atmosphere. The heating rate during pyrolysis was 8°C / min. After the temperature reached 400°C, it was kept warm for 3 hours and then naturally cooled to room temperature to obtain the original coffee grounds biochar.

[0051] The original coffee grounds biochar was mixed with iron slag in a mass ratio of 2:1, put into a nitric acid solution prepared with ultrapure water and concentrated nitric acid in a volume ratio of 1:1, and allowed to stand for 6 hours. Then it was taken out and dried and put into a tubular furnace for a second pyrolysis under a nitrogen atmosphere. The heating rate during pyrolysis was 8°C / min. After the temperature reached 800°C, it was kept warm for 3 hours and then naturally cooled to room temperature to obtain an iron slag biochar composite material.

[0052] Example 3

[0053] The ramie stalks were naturally air-dried and then ground and sieved. The ramie stalk residue powder between 100 mesh and 200 mesh was put into a tubular furnace and pyrolyzed for the first time under a nitrogen atmosphere. The heating rate during pyrolysis was 7°C / min. After the temperature reached 420°C, it was kept warm for 2.5 hours and then naturally cooled to room temperature to obtain the original ramie stalk biochar.

[0054] The original ramie stalk biochar was mixed with iron slag in a mass ratio of 3:1, put into a nitric acid solution prepared with ultrapure water and concentrated nitric acid in a volume ratio of 1:1, and allowed to stand for 8 hours. Then it was taken out and dried and put into a tubular furnace for a second pyrolysis under a nitrogen atmosphere. The heating rate during pyrolysis was 10°C / min. After the temperature reached 850°C, it was kept warm for 2 hours and then naturally cooled to room temperature to obtain an iron slag biochar composite material.

[0055] Comparative Example 1

[0056] The sawdust was naturally air-dried and then ground and sieved. The sawdust residue powder between 100 mesh and 200 mesh was put into a tubular furnace and pyrolyzed for the first time under a nitrogen atmosphere. The heating rate during pyrolysis was 10°C / min. After the temperature reached 500°C, it was kept warm for 2h and then naturally cooled to room temperature to obtain the original sawdust biochar, named 500BC.

[0057] Performance Testing

[0058] Experiment 1: Prepare a mixed solution of trivalent arsenic (As(III)) and butyl xanthate (Bx), wherein the concentration of trivalent arsenic in the mixed solution is 20 mg / L, and the concentration of butyl xanthate in the mixed solution is 50 mg / L. Take two beakers, record them as A and B, add 50 mL of the mixed solution of trivalent arsenic and butyl xanthate to the two beakers respectively, then add 10 mg of ISBC prepared in Example 1 and 0.5 mL of a peroxydisulfate solution with a concentration of 2 mmol / L to beaker A, and add 10 mg of 500BC prepared in Comparative Example 1 and 0.5 mL of a peroxydisulfate solution with a concentration of 2 mmol / L to beaker B. After reacting for 1 hour, the removal rates of trivalent arsenic and butyl xanthate were measured, and the results are shown in Table 1.

[0059] Table 1 Removal rates of trivalent arsenic and butyl xanthate

[0060] A beaker Beaker B Butyl xanthate removal rate 99.8% 1.4% Removal rate of trivalent arsenic 99.7% 1.2%

[0061] As shown in Table 1, the removal rate of butyl xanthate and trivalent arsenic in water by the iron slag biochar composite material prepared by the present invention is as high as 99% or more within a reaction time of 1 hour, which is far higher than the activation capacity of peroxydisulfate by the original sawdust biochar (500BC). This indicates that the iron slag biochar composite material prepared by the present invention is an effective and low-cost material for removing trivalent arsenic and butyl xanthate.

[0062] Figure 2This is a SEM image of the iron slag biochar composite material prepared in Example 1 after persulfate activation to remove trivalent arsenic and butyl xanthate. Figure 1 From the comparison of Figure a, it can be seen that after reacting with trivalent arsenic and butyl xanthate, the surface of the iron slag biochar composite material becomes rougher, indicating that trivalent arsenic or butyl xanthate and its degradation products may be adsorbed on the surface of the iron slag biochar composite material.

[0063] Experiment 2: Prepare a mixed solution of trivalent arsenic (As(III)) and butyl xanthate (Bx), wherein the concentration of trivalent arsenic in the mixed solution is 20 mg / L, and the concentration of butyl xanthate in the mixed solution is 50 mg / L. Add 50 mL of the above mixed solution to a beaker, then add 10 mg of ISBC prepared in Example 1 and 0.5 mL of a 2 mmol / L persulfate solution, and conduct experiments at pH values ​​of 3, 5, 7, 9, and 11, respectively. After 1 hour of reaction, the removal rates of trivalent arsenic and butyl xanthate are measured. The data results are as follows: Figure 3 and Figure 4 As shown. Figure 3 and Figure 4 It is found that under different pH conditions, the iron slag biochar composite material prepared by the present invention has good activation ability for peroxydisulfate, and achieves efficient removal of butyl xanthate and trivalent arsenic. It can be seen that the iron slag biochar composite material prepared by the present invention can stably produce catalytic effects in a wide range of pH values, and has great potential in the application of actual water bodies.

[0064] Experiment 3: preparing a mixed solution 1 of trivalent arsenic (As(III)) and butyl xanthate (Bx), wherein the concentration of trivalent arsenic in the mixed solution 1 is 20 mg / L, and the concentration of butyl xanthate in the mixed solution 1 is 100 mg / L;

[0065] A mixed solution 2 of trivalent arsenic (As(III)) and butyl xanthate (Bx) is prepared, wherein the concentration of trivalent arsenic in the mixed solution 2 is 20 mg / L, and the concentration of butyl xanthate in the mixed solution 2 is 50 mg / L;

[0066] A mixed solution 3 of trivalent arsenic (As(III)) and butyl xanthate (Bx) is prepared, wherein the concentration of trivalent arsenic in the mixed solution 3 is 20 mg / L, and the concentration of butyl xanthate in the mixed solution 3 is 20 mg / L;

[0067] A mixed solution 4 of trivalent arsenic (As(III)) and butyl xanthate (Bx) is prepared, wherein the concentration of trivalent arsenic in the mixed solution 4 is 50 mg / L, and the concentration of butyl xanthate in the mixed solution 4 is 20 mg / L;

[0068] A mixed solution 5 of trivalent arsenic (As(III)) and butyl xanthate (Bx) is prepared, wherein the concentration of trivalent arsenic in the mixed solution 5 is 50 mg / L, and the concentration of butyl xanthate in the mixed solution 5 is 50 mg / L;

[0069] A mixed solution 6 of trivalent arsenic (As(III)) and butyl xanthate (Bx) is prepared, wherein the concentration of trivalent arsenic in the mixed solution 6 is 100 mg / L, and the concentration of butyl xanthate in the mixed solution 6 is 20 mg / L;

[0070] A mixed solution 7 of trivalent arsenic (As(III)) and butyl xanthate (Bx) is prepared, wherein the concentration of trivalent arsenic in the mixed solution 7 is 10 mg / L, and the concentration of butyl xanthate in the mixed solution 7 is 50 mg / L;

[0071] A mixed solution 8 of trivalent arsenic (As(III)) and butyl xanthate (Bx) is prepared, wherein the concentration of trivalent arsenic in the mixed solution 8 is 10 mg / L, and the concentration of butyl xanthate in the mixed solution 8 is 100 mg / L;

[0072] A mixed solution 9 of trivalent arsenic (As(III)) and butyl xanthate (Bx) is prepared, wherein the concentration of trivalent arsenic in the mixed solution 9 is 50 mg / L, and the concentration of butyl xanthate in the mixed solution 9 is 100 mg / L;

[0073] Prepare trivalent arsenic (As(III)) solutions with concentrations of 50 mg / L and 100 mg / L respectively;

[0074] Butyl xanthate (Bx) solutions with concentrations of 50 mg / L and 100 mg / L were prepared respectively.

[0075] Take 50 mL of each of mixed solution 1, mixed solution 2, mixed solution 5, mixed solution 7, mixed solution 8, mixed solution 9, 50 mg / L butyl xanthate (Bx) solution and 100 mg / L butyl xanthate (Bx) solution, add 10 mg of ISBC prepared in Example 1 and 0.5 mL of 2 mmol / L peroxydisulfate solution, respectively, and measure the removal rate of butyl xanthate after reacting for 1 hour. The data results are as follows: Figure 5 As shown;

[0076] Take 50 mL of each of mixed solution 1, mixed solution 2, mixed solution 3, mixed solution 4, mixed solution 5, mixed solution 6, a 50 mg / L trivalent arsenic (As(III)) solution, and a 100 mg / L trivalent arsenic (As(III)) solution, add 10 mg of ISBC prepared in Example 1 and 0.5 mL of a 2 mmol / L peroxydisulfate solution, respectively, and react for 1 hour to measure the removal rate of trivalent arsenic. The data results are as follows: Figure 6 shown.

[0077] Depend on Figure 5 and Figure 6 It can be seen that the iron slag biochar composite material prepared by the present invention has a very obvious treatment effect on the mixed contaminated solution of As(III) and butyl xanthate, especially in the mixed solution, the removal rate of butyl xanthate is significantly improved, that is to say, the iron slag biochar composite material has a very obvious effect on the activation of peroxydisulfate, and has great application potential in dealing with actual water bodies with multiple pollution.

[0078] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0079] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An application of an iron slag biochar composite material in activating persulfate and removing trivalent arsenic and butyl xanthate simultaneously, characterized in that: The preparation method of the iron slag biochar composite material comprises the following steps: The biomass is subjected to a first pyrolysis to obtain raw biochar; the raw biochar is acidified and mixed with iron slag and then subjected to a second pyrolysis to obtain an iron slag biochar composite material; The first pyrolysis and the second pyrolysis are both carried out in a protective gas.

2. The use according to claim 1, characterized in that: The biomass is one or more of ramie stalks, ramie silk, wood chips and coffee grounds; the particle size of the biomass is 50-200 meshes.

3. The use according to claim 1, characterized in that: The temperature of the first pyrolysis is 300-500°C, and the time of the first pyrolysis is 2-3h; the heating rate from room temperature to the temperature of the first pyrolysis is 5-10°C / min.

4. The use according to any one of claims 1 to 3, characterized in that: The iron slag is the iron-containing surface layer that falls off the surface of factory smelting waste.

5. The use according to claim 4, characterized in that: The mass ratio of the original biochar to the iron slag is 1-5:

1.

6. The use according to claim 5, characterized in that: The specific operation steps of the acidification mixing are: putting the original biochar and iron slag into a mixed solution of concentrated nitric acid and water, until the mixed solution covers the original biochar and the iron slag, and standing for 4 to 12 hours; the volume ratio of the concentrated nitric acid to water is 1 to 3:1, and the concentration of the concentrated nitric acid is 2.4 to 7.2 mol / L.

7. The use according to claim 1 or 3 or 5 or 6, characterized in that: The temperature of the second pyrolysis is 500-900°C, and the time of the second pyrolysis is 2-3h; the heating rate from room temperature to the temperature of the second pyrolysis is 5-10°C / min.

8. The use according to claim 7, characterized in that: The protective gas is any one of nitrogen, helium, neon and argon.

Citation Information

Patent Citations

  • Preparation method and application of novel magnetic microalgae-based complexing agent

    CN110898812A

  • Iron-based biochar composite material as well as preparation method and application thereof

    CN113426415A

Cited By

  • Method for preparing seaweed biochar composite material from expired milk powder, obtained product and application

    CN118179560A

  • Method for preparing seaweed biochar composite material using expired milk powder and the resulting product and applications

    CN118179560B